Morphometric Formula for Field Determination of the Sex of Steppe Eagle (Aquila nipalensis) Nestlings in Altai-Sayan Region - Natalya G. Andreyenkova; Maria A. Shalnova; Igor V. Karyakin; Elena P. Shnayder (Пернатые хищники и их охрана)
Rapid sex determination of Steppe Eagle (Aquila nipalensis) nestlings without laboratory diagnostics is necessary for a variety of tasks. When working directly on a nest, it is important to know the sex of nestlings during population monitoring, ringing and tagging with GPS transmitters. Sex determination is also necessary when working with sick and injured birds, in rehabilitation centers, which do not always have the opportunity and time for genetic analysis. Experienced ornithologists in most cases can quite accurately determine the sex of nestling by eye, but this does not always work, and not all researchers have sufficient experience. The Steppe Eagle has a noticeable sexual dimorphism in size, which is well manifested even in 45-day-old nestlings.